Design and Construction of an Automatic Mosque Locking System Using Internet of Things (IoT) Technology with An-droid Smartphone Control - Imam Tri Suryadin (Journal of Engineering, Electrical and Informatics, 2025)
The continuous evolution of the Internet of Things (IoT) has significantly transformed how devices interact and exchange information, enabling automation in various fields, including facility security systems. Mosques, as community-based facilities, still rely heavily on manual locking mechanisms that are time-consuming and prone to human error or key loss. This study presents the design and implementation of an IoT-based automatic mosque locking system that can be monitored and controlled via an Android smartphone. The system architecture integrates a NodeMCU ESP8266 microcontroller as the central control unit, a relay module to activate a servo-powered door lock, and a magnetic reed sensor to identify door status. Communication between the hardware and mobile interface is established using the MQTT protocol connected through the Blynk IoT cloud platform. Experimental evaluation confirms that the system can perform remote locking and unlocking within an average latency of 1–2 seconds, depending on Wi-Fi signal strength. Furthermore, the system provides automatic status updates and notifications when the door is opened or closed. The prototype demonstrates reliable performance, energy efficiency, and ease of use for mosque administrators. In conclusion, the proposed IoT-based smart lock solution successfully enhances mosque security management and shows promising potential for wider adaptation to other public facilities requiring secure and remotely accessible control systems.